The Role of Receiving Technology on Employee Performance: Job Satisfaction as Mediation - Abdullah W. Jabid; Rinto Syahdan; Johan Fahri; Irfandi Buamonabot (Journal of Indonesian Economy and Business, 2023)
Introduction/Main Objectives: The development of information technology today has resulted in the acceptance of technology being strongly influenced by transformational leadership, system quality, and facilitating conditions, as well as how it can affect employee performance and job satisfaction. Background Problems: Research on how job satisfaction mediates the relationship between employee performance and acceptance still needs to be improved. This research discusses how transformational leadership, facilitating conditions, and system quality shape technology acceptance and employee performance, primarily determined by job satisfaction, especially the mediating effect of job satisfaction on the relationship between technology acceptance and employee performance. Novelty: Inconsistencies both in theory and empirically making it necessary to re-test transformational leadership, system quality, and conditions that facilitate technology acceptance and analyze the effect of technology acceptance on employee performance through job satisfaction, both directly and indirectly, in a study of the Ternate City Government. Research Method: 117 respondents were involved in this study. The respondents were determined through purposive sampling. The data were analyzed using partial least squares (PLS) version 3. Seven hypotheses were proposed in this study. Findings: The research findings indicate that system quality and facilitating conditions can predict technology acceptance and employee performance can predict job satisfaction. The results of this study confirm the indirect mediating function of job satisfaction in the relationship between technology acceptance and employee performance. Conclusion: The Municipal Government of Ternate must improve system information management and offer even better facilitating conditions for implementation to increase the acceptance of the technology.